Dry matter intake and ruminal fermentation parameters in goats fed sugarcane in replacement of corn silage - Canizares, Gil Ignácio Lara; Gonçalves, Heraldo Cesar [UNESP]; Marques, Raquel Ornelas [UNESP]; Lourençon, Raquel Vasconcelos; Gomes, Helen Fernanda Barros; Boaventura Neto, Oscar; Canizares, Marleide Costa (FapUNIFESP (SciELO), 2021)
The trial was conducted with the objective to evaluate fresh sugarcane as a replacement for corn silage on dry matter intake, ruminal parameters (pH, short chain fatty acids, and ammonia nitrogen concentration), and degradation kinetics of forages and concentrate in maintenance adult goats. Four nonlactating ruminally cannulated goats were used in a 4 X 4 Latin square design with the replacement of 0, 33, 67, and 100% of corn silage by sugarcane as the independent variable. The substitution of sugarcane for corn silage did not affect dry matter intake, daily weight gain, or ruminal pH. A quadratic effect was observed for ammonia nitrogen concentration with a maximum concentration at 74.43% of sugarcane inclusion, as well as for short chain fatty acids, with maximum concentrations of acetate and butyrate at 0.59 and 32.70% of sugarcane inclusion, respectively. The minimum concentration of propionate was verified on 10.36% of sugarcane inclusion. However, the acetate:propionate ratio linearly decreased with increased sugarcane content. No effect was observed of different rumen environments on forage dry matter and neutral detergent fiber degradability (effective and potential degradability, soluble and potential degradable fractions). Dry matter degradability was 66.79% for sugarcane and 72.62% for corn silage after 96 h of incubation. Neutral detergent fiber was 37.10 and 51.82% for sugarcane and corn silage, respectively, after 96 h of incubation. In conclusion, sugarcane can be used as a replacement for corn silage in maintenance adult goats feed without altering dry matter intake and forage degradability while increasing propionate production.
Parâmetros de ingestão de matéria seca e fermentação ruminal em cabras alimentadas com cana-de-açúcar em substituição à silagem de milho
Keywords: ammonia nitrogen; degradabilidade; degradability; dry matter; matéria seca; nitrogênio amoniacal; short chain fatty acids; ácidos graxos de cadeia curta